End the Recruitment Crisis! - Christian Merkl; Enzo Weber (Wirtschaftsdienst)
Abstract In contrast to the economic and financial crisis of 2009, the labour market has been hit harder during the coronavirus crisis in 2020. New hires have declined substantially, which may lead to persistent unemployment and a “generation COVID-19” of graduates. Employment subsidies would be a suitable measure to stabilise the economy and the labour market and to reduce these risks at an early stage.